Drive operability research for manual drill machine; Scientific research of the SCO countries: synergy and integration; Pt. 4, Beijing, 10 April - Korotkov V. S. Vladimir Sergeevich (2024, 2024)
As a result of the work, the stresses in the separator partitions were determined in the Solid Works program depending on the load on the output shaft of the gearbox. The results of bench tests of a manual electric drill drive based on a commutator motor with a power consumption of 1.5 kW with a rated armature rotation speed of 15,000 rpm and with a wave transmission with intermediate rolling elements with a gear ratio of 59 are presented. The vibration levels of the drive on the gearbox housing and on the handles. A limit value has been established for the efficiency of the wave gearbox at the rated speed of the motor armature